we need to write the equation of the graph
it is a parable then the general form is
![y=(x+a)^2+b](https://img.qammunity.org/2023/formulas/mathematics/college/6wlkvwl9xq87vdzk9xgv7xzvnllngoiglg.png)
where a move the parable horizontally from the origin (a=negative move to right and a=positive move to left)
and b move the parable vertically from the origin (b=negative move to down and b=positive move to up)
this parable was moving from the origin to the right 2 units and any vertically
then a is -2 and b 0
![y=(x-2)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/p39nsp512tk3847o6aa9ca0xx07hgl58jp.png)
now we have the system of equations
![\begin{gathered} y=3x-2 \\ y=(x-2)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/htv3ytr83qiwe922t7h28mbj56msegeeq9.png)
we can replace the y of the first equation on the second and give us
![3x-2=(x-2)^2](https://img.qammunity.org/2023/formulas/mathematics/college/n8ooeg0rrfmo736q3kvjkr7haqnxw0k8fl.png)
simplify
![3x-2=x^2-4x+4](https://img.qammunity.org/2023/formulas/mathematics/college/xmbyqckz66ieeuk2b750hv2j4egqgw9l1q.png)
we need to solve x but we have terms sith x and x^2 then we can equal to 0 to factor
![\begin{gathered} 3x-2-x^2+4x-4=0 \\ -x^2+7x-6=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7z744lfwb5ft8j45od1u1o0e3n9ezf9r0c.png)
multiply on both sides to remove the negative sign on x^2
![x^2-7x+6=0](https://img.qammunity.org/2023/formulas/mathematics/college/hrxx7zffxc4c89zltgirb2se5d8fsaz0pq.png)
now we use the quadratic formula
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
where a is 1, b is -7 and c is 6
![\begin{gathered} x=\frac{-(-7)\pm\sqrt[]{(-7)^2-4(1)(6)}}{2(1)} \\ \\ x=\frac{7\pm\sqrt[]{49-24}}{2} \\ \\ x=\frac{7\pm\sqrt[]{25}}{2} \\ \\ x=(7\pm5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1c4w67ts66w8dnb73wph85wdrn2sromdrv.png)
we have two solutions for x
![\begin{gathered} x_1=(7+5)/(2)=6 \\ \\ x_2=(7-5)/(2)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gu6jo8n5mgsjkfac1vtyb494zndimz6jqv.png)
now we replace the values of x on the first equation to find the corresponding values of y
![y=3x-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/cs951ld0m5fyz30f6jmmjk2jhieli70v8l.png)
x=6
![\begin{gathered} y=3(6)-2 \\ y=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lvrjd0ky2h2mpc59sgwwrlz7uos6emg03x.png)
x=1
![\begin{gathered} y=3(1)-2 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ihg0ebawvw710xgdy1mmku4mrmx9oai9m1.png)
Then we have to pairs of solutions
![\begin{gathered} (6,16) \\ (1,1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/llwaixyokmr9pco9x4bcwp4r1n79vws35n.png)
where green line is y=3x-2
and red points are the solutions (1,1)and(6,16)